Community Economic Empowerment in Achieving National Defense - Supandi, Supandi; Sahabuddin, Zaenal Abidin; Amperiawan, Gita (The Republic of Indonesia Defense University, 2016)
Economic empowerment is an effort to improve society's ability to fulfill their needs and have well-being, it can influence the improvement of national defense. The research purpose is analyzing the actual conditions and factors affecting the implementation of economic empowerment in South Tangerang city. This research used qualitative descriptive method. Collected data through observation, interviews and focus group discussions. All data have been obtained processed with data reduction, data presentation and conclusion. Results showed that the economic empowerment in South Tangerang City, conducted by the city government and stekholder (Office, Business Associations, Banks, Universities and Private Entrepreneurs) although not yet collaborate to achieve expected results